2001
DOI: 10.1143/jjap.40.5497
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Properties of Mg Doped (Ba0.5Sr0.5)TiO3 Thin Films

Abstract: The microstructures and electrical characteristics of Mg doped (Ba0.5Sr0.5)TiO3 (BSTM) thin films were investigated as a function of Mg content. Also the multi-layered structure, BSTM/BST/BSTM was proposed to improve both of the leakage current and dielectric constant. With increasing Mg content, the perovskite peak intensity slightly decreased and grains became smaller. For the films above 15 mol% Mg, the secondary phase (MgTi2O5) was observed in X-ray diffraction (XRD) patterns. The dielectric constant decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
29
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 15 publications
7
29
1
Order By: Relevance
“…This two-folded effect would lead to the diffraction peaks hardly shift [11]. It was observed that Mg 2+ ions initially entered into the A sites of perovskite structure, then into the B sites when the Mg 2+ concentration exceeds 5 at% in the barium strontium titanate and up to the solubility limit (~15 at%) [12]. The concentration of Mg 2+ in our samples preponderates over the solubility limit of Mg 2+ in BaTiO 3 , so the diffraction peak position does not change when the content of BaMg 6 Ti 6 O 19 increases from 10 to 60 wt%.…”
Section: Resultsmentioning
confidence: 99%
“…This two-folded effect would lead to the diffraction peaks hardly shift [11]. It was observed that Mg 2+ ions initially entered into the A sites of perovskite structure, then into the B sites when the Mg 2+ concentration exceeds 5 at% in the barium strontium titanate and up to the solubility limit (~15 at%) [12]. The concentration of Mg 2+ in our samples preponderates over the solubility limit of Mg 2+ in BaTiO 3 , so the diffraction peak position does not change when the content of BaMg 6 Ti 6 O 19 increases from 10 to 60 wt%.…”
Section: Resultsmentioning
confidence: 99%
“…The NiO-BaTiO 3 composites had been reported by some researchers [2][3][4][5][6][7][8][9]. It is indicated that Ni 2+ reduces the dielectric loss and leakage-current particularly [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…It is indicated that Ni 2+ reduces the dielectric loss and leakage-current particularly [5][6][7]. And the NiO inclusion inhibits the grain growth of BaTiO 3 observably [8,9], although only a small amount of Ni 2+ can dissolve into the perovskite phase of BaTiO 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [8] also found an increase in the dielectric constant of the multilayer films with a decrease in the sublayer thickness. Yoon et al [9] found that a high dielectric constant and low leakage current could be obtained in BSTM/BST/BSTM multilayered films by adjusting the thickness of the sublayers.…”
Section: Introductionmentioning
confidence: 99%